Parkinson's disease - a significant neurological challenge. Current knowledge of etiology, diagnosis and treatment - Bednarz, Lucjan; Woś, Natalia; Bialic, Kinga; Bialic, Artur; Bakalarczyk, Rafał; Majewski, Paweł; Szala-Czerwonka, Karolina; Wijas, Karolina; Rejmer, Adrian; Rojek, Katarzyna (Journal of Education, Health and Sport, 2023)
Introduction: Parkinson's disease is one of the most common neurodegenerative disorders, affecting several million people worldwide. In the current diagnosis, the most important thing is to watch for individual symptoms, which appear at different stages of the disease and can worsen over time. The wide variation in symptoms may suggest that they are the result of other diseases. It is a disease with an unknown underlying cause, and is incurable. Aim of the study: Summary of current knowledge regarding diagnosis and treatment of Parkinson's disease. Material and methods: Review of articles from the PubMed database using the following terms: “Parkinson's disease”, “diagnosis”, “treatment”, “genetics”, “levodopa”, ”α-synuclein”. Results: The diagnosis of Parkinson's disease is still based on the clinical picture of the patient. In recent years, research has been underway to develop new biomarkers for the disease that would allow faster detection. The treatment used is based on delaying the progression of the disease and its symptoms. Treatment mainly involves levodopa with carbidopa and drugs to reduce the severity of individual symptoms, in some cases surgical methods are used. Conclusions: Parkinson's disease poses a challenge to doctors because of its unknown cause and incurability. In recent years, a lot of new information has emerged about factors contributing to its onset, such as genetic factors. Treatment, which is mainly based on pharmacotherapy, should be enriched to a greater extent with physical activity adapted by specialists, physiotherapy treatments and also speech exercises, with the aim of making it easier to cope with bothersome symptoms and improve daily life.